Analysis of Students' Differentiating, Organizing, and Attributing Skills in Solving High School Chemistry Problems: Rasch Modeling - Ranjani, Intan Salsabila Putri; Laliyo, Lukman Abdul Rauf; Sihaloho, Mangara; Isa, Ishak; Tangio, Julhim S.; Najmah, Najmah; Thayban, Thayban; Kurniawati, Erga (Universitas Negeri Gorontalo, 2026)
This study aims to analyze the ability of XII grade high school students in solving C4 level chemistry problems based on three indicators (Differentiating, Organizing, and Attributing) using Rasch modeling. This research is a quantitative study with a non-experimental research design (survey). The results showed that the level of analyzing students with an overall percentage reached 44.3%. Analysis based on indicators, Differentiating ability reached 47.06% (sufficient category), Organizing was at 44.88% (sufficient category), and Attributing also reached 40.56% (sufficient category). The ability to analyze students in SMAN A had an average value of 0.94, SMAN B had an average value of 0.11, SMAN C had an average value of -0.09, SMAN D had an average value of -0.62 SMAN E had an average value of -0.96, SMAN F had an average value of -0.25, SMAN G had an average value of 0.18, SMAN H had an average value of -0.62, while SMAN I had an average value of -0.73.